The management of chronic liver disease, including transplantation 1 - McCashland, Timothy M. (Henry Stewart Talks, 2021)
Management of common complications associated with end stage liver disease, Evaluation and management of ascites, Evaluation and management of variceal bleeding, Diagnosis of hepatic encephalopathy, Preparation for evaluation and listing for liver transplantation